2018
DOI: 10.3389/fonc.2018.00572
|View full text |Cite
|
Sign up to set email alerts
|

Language-Eloquent White Matter Pathway Tractography and the Course of Language Function in Glioma Patients

Abstract: Object: As various recent studies show, damage to white matter pathways leads to permanent functional deficits in a high percentage of patients. Particularly the subcortical language network is complex, and its visualization has a tremendous relevance for neurosurgeons. This pilot study aims to correlate language-eloquent white matter pathways with the course of language function after the resection of left-sided perisylvian gliomas.Methods: We included 10 patients who underwent resection of highly language-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
0
28
0
1
Order By: Relevance
“…Acute deficits reported immediately after surgery involving the FAT were aphasia, impairment of speech, self-initiated speech disorders, speech hesitancy, numerous pauses and delays during conversation, anomia, delays in naming and word finding difficulties, errors in verb generation tasks, perseverations, need for phonological cues, errors with reading, delay in counting, and simple calculations ( 35 , 46 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute deficits reported immediately after surgery involving the FAT were aphasia, impairment of speech, self-initiated speech disorders, speech hesitancy, numerous pauses and delays during conversation, anomia, delays in naming and word finding difficulties, errors in verb generation tasks, perseverations, need for phonological cues, errors with reading, delay in counting, and simple calculations ( 35 , 46 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the results of DES, navigated repetitive transcranial magnetic stimulation (nrTMS) has evolved to be a reliable tool for the non-invasive determination of language-negative sites [ 5 , 6 , 7 , 8 ]. The combination of nrTMS-based regions of interest (ROIs) with tractography algorithms has been shown to be an option for the visualization of the subcortical language network, since its correlation with the clinical status of patients has been approved [ 9 , 10 ]. Intraoperative neurophysiology, starting with nrTMS and its successful combination as an adjunct and guide for awake craniotomies, has recently been demonstrated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the brain structural network of patients with brain disorders (including stroke, cerebrovascular disease, and tumor‐related lesions) may be disrupted, some of which are related to cognitive dysfunction (Du et al., 2019; Ille, Engel, Kelm, Meyer, & Krieg, 2018; Urbanski et al., 2011). Despite a growing body of the literature on examining tumor‐affected brains through DTT technique (Abhinav, Yeh, Mansouri, Zadeh, & Fernandez‐Miranda, 2015; Conti Nibali et al., 2019; Incekara et al., 2018), a few studies have endeavored to study the effects of glioma from a whole‐brain perspective.…”
Section: Introductionmentioning
confidence: 99%